B and T lymphocyte attenuator (BTLA) and PD-1 pathway dual blockade promotes antitumor immune responses by reversing CD8+ T-cell exhaustion in non-small cell lung cancer - Zhang, Yang; Yang, Yang; Zeng, Yuanyuan; Qu, Qiuxia; Shen, Dan; Mu, Chuanyong; Lei, Wei; Su, Meiqin; Mao, Jingyu; Gao, Lirong; Liu, Zeyi; Chen, Cheng; et al. (Frontiers in Immunology, 2025)
BackgroundImmunotherapies targeting the programmed cell death 1 (PD-1)/programmed death ligand 1 (PD-L1) have shown great promise for a subset of patients with non-small cell lung cancer (NSCLC). However, safe and robust combination therapies are still needed to bring the benefit to broader patient populations.Methodswe performed in vivo treatment with PD-L1 antibody in Lewis lung carcinoma (LLC)-derived murine NSCLC model. Expression of B and T lymphocyte attenuator (BTLA) was detected during treatment. We evaluated the effects of the combination of anti-BTLA and anti-PD-L1 mAbs on tumor growth and overall survival of mice. In addition, distribution and function of immune cells were analyzed by flow cytometry. The role of BTLA in human and murine CD8+ T cells and its impact on reversing exhausted phenotype of PD-1+CD8+ T cell by PD-L1 blockade were analyzed. Furthermore, we investigated expression and distribution of BTLA on lymphocytes in tumor microenvironment of different specimens from NSCLC patients.ResultsThere was no significant difference overall survival between anti-PD-L1 therapy and IgG in LLC-bearing mice, and BTLA expression was increased on CD8+ T cells after PD-L1 antibody treatment. LLC-bearing mice treated with combination of anti-BTLA and anti-PD-L1 therapy had an improved overall survival than anti-BTLA or anti-PD-L1 alone. Compared to monotherapy with anti-BTLA or anti-PD-L1, mice treated with combination therapy demonstrated increased infiltration of CD8+ and CD4+ T cells, as well as increased expression of IFN-γ, TNF-α and Ki-67 in CD8+ T cells. In addition, CD8+ T cells co-expressing BTLA and PD-1 exhibited the most exhausted phenotype to resist PD-L1 blockade therapy. Furthermore, BTLA+CD8+ T cells were abnormally increased in different specimens from NSCLC patients, and CD8+ T cells expressing BTLA in NSCLC microenvironment were correlated with clinical response to anti-PD-1 therapy in NSCLC patients.ConclusionOur results show that BTLA and PD-1 cooperatively inhibit the activity of CD8+ T cells and are associated with resistance to PD-1/PD-L1 pathway blockade in NSCLC patients. Anti-BTLA blockade enhances the antitumor efficacy of anti-PD-L1 therapy. Dual BTLA and PD-1/PD-L1 blockade should be further explored to elicit potent antitumor CD8+ T-cell responses in NSCLC patients.